NATIONALISM, NATION AWARENESS AND PAST IMAGINATION (A REFLECTIONS OF 65 YEAR HISTORY OF INDEPENDENT INDONESIA) - Abdulah, Anzar (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2011)
Allegations are often made ahead of the Proclamation of Independence of Indonesia, among others, is increasingly fading spirit of nationalism among the younger generation. Allegations are not necessarily true, but it has created a stigma in society. It needs to be clarified by outlining the background of the birth of nationalism and nationalism contextualization in conjunction with modern Indonesian society today. Nationalism is a long process of the dialectic between space, time and social groups, as well as the political process. Although there are its relation with the "birth", nationalism has always been the "birth process". Nationalism is a modern phenomenon, a notion of nationhood was born out of the equation the fate and suffering as a result of colonization, thus was born the solidarity for the nation rise up and liberate themselves from colonialism to freedom and independence. When the standards of nationalism were patriotism and physical struggle, like war of independence first, certainly has a point, that the nationalism awareness of youth today is fading. However, it should be explained that now no longer possible to perform a physical struggle full of heroism like the past, but we now need is the social solidarity that can strengthen the social bonds of nationhood and Indonesianness in charge of this independence nature. This is what needs to be grown and developed because these valuesÂ are now beginning to fade among the younger generation, the community and the nation's elite. Nationalism is not something static, but full of dynamics. Every era has different conditions and challenges, thus requiring a dynamic form of nationalism. This paper aims to analyze the relationship between nationalism, nation awareness, and the memories of the past as a reflection of history after 65 years of Indonesia Independent. Also as re-introspection ourselves as a nation, how far nationalism that has made us stronger in strengthening of Indonesianness nodes.